Clinician and patient perspectives on screening mammography among women age 75 and older: A pilot study of a novel decision aid - Dejana Braithwaite; Anthony Chicaiza; Katherine Lopez; Kenneth W. Lin; Ranit Mishori; Shama D. Karanth; Stephen Anton; Kristen Miller; Mara A. Schonberg; Nancy L. Schoenborn; Suzanne C. O'Neill (Elsevier, 2023)
Objective: Supporting patient-clinician communication is key to implementing tailored, risk-based screening for older adults. Objectives of this multiphase mixed methods study were to identify factors that primary care clinicians consider influential when making screening mammography recommendations for women ≥75 years, develop a patient decision aid that incorporates these factors, and gather feasibility and acceptability from the patients' perspective. Methods: Clinicians from a Mid-Atlantic practice network completed online surveys. Women in the same network completed surveys before and after receiving a tailored booklet that included information about the benefits and harms of screening for women ≥ 75 years, a breast cancer risk-estimate, and a question prompt list to support patient-clinician communication Results: Clinicians (N=21) were primarily women [57.1%] and practiced family medicine [81.0%]. They cited patients' age ≥75 years [95.4%], comorbidity [86.4%], functional status [77.3%], cancer family history [63.6%], U.S. Preventive Services Task Force guidelines [81.8%] and new research [77.3%] as factors influencing their recommendations. Fourteen women completed baseline surveys and received personalized decision aids (Mean age=79.1 years). Eleven completed the post-intervention survey. All were satisfied with the booklet length, 81.8% found the booklet easy to understand and 72.7% helpful in decision-making Perceived lifetime breast cancer risk decreased significantly from pre- to post-intervention (p = 0.02). Conclusions: Results suggest this decision aid, which incorporates key decisional factors from the clinician's perspective, is feasible and acceptable to patients. Innovation: A tailored decision aid booklet is innovative as it provides information on personalized risk and potential benefits and harms to older women considering screening.